KOMUNIKASI PEMASARAN PARIWISATA KOMUNITAS GENPI (GENERASI PESONA INDONESIA) DALAM MEMPROMOSIKAN BRAND DESTINASI PASAR SITI NURBAYA - Idrus, Muhammad; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The phenomenon of esteem as if it were the priority needs of today’s society. The society, especially young people, need something new to meet the need for satisfaction. The GenPI West Sumatera Community formed by Tourism Department RI was present in the society and initiated a digital destination called Pasar Siti Nurbaya. Pasar Siti Nurbaya as the concept of a new tourist destination in West Sumatera serves to facilitate the society to fulfill esteem by offering attractive selfie photo spots, traditional Minangkabau culinary and regional dance art performances. This study aims to find out how digital destinations, positioning strategies, differentiation, destination branding and tourism marketing communication strategies are carried out by The GenPI West Sumatera Community in promoting the Siti Nurbaya market destination brand.This study used qualitative research methods. The research subjects were eight people who were selected using purposive techniques, the main informants in this study amounted to 4 people from The GenPI West Sumatera Community and 2 people from the West Sumatra Provincial Tourism Office and 2 people from the society as supporting informants. Data collection is done through interviews, observation and documentation. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluations by using data validity checking techniques are extended participation and triangulation.The results of this study indicate that the form of digital destinations that the GenPI West Sumatra Community adheres to uses the market concept called Pasar Siti Nurbaya. Whereas the destination positioning consists of targets, namely "Kids Zaman Now", promotional media, namely social media and the tagline, "Pasar Zaman Now". Differentiation of destinations is an Instagramable destination. Branding destination consists of a logo brand, brand name, namely Siti Nurbaya, brand tagline, the "Pasar Zaman Now". The GenPI Community Tourism Marketing Communication Strategy in West Sumatra uses the marketing communication mix theory consisting of using media as a means of promotion and participating in various events around tourism.Keyword: Marketing communication, tourism, brand, digital, destination.